Peramalan Hasil Penjualan Perhiasan Emas Menggunakan Metode Exponential Smoothing (Studi Kasus: Toko Emas Rejeki Baru Sumenep) - Risqi Auliatin Nisyah; Nurul Hidayat; Ahmad Afif Supianto (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Gold is a precious metal which is one of the important roles in people's daily lives. Gold jewelry is usually sold in large places such as markets to small shops. The rise and fall of the sales of gold obtained by the seller is difficult to predict, one of the contributing factors is the uncertain gold price following the fluctuation of the rupiah exchange rate against the dollar. Though knowing the results of future sales can help the seller to know the benefits and losses in the coming period. Therefore, it takes a system that functions to do forecasting to find out the results of automatic gold sales with the Exponential Smoothing method which is one of the forecasting methods that can perfect a forecasting result by smoothing on past values ​​that function to produce forecasting values. Then, error evaluation of forecasting results was performed with Mean Absolute Percentage Error (MAPE). The lowest MAPE results obtained were located in the SES method when the parameter α = 0.4 with a value of 56.64. Based on the MAPE value that has been obtained using the three methods on Exponential Smoothing, the results obtained above 50, then the Exponential Smoothing method is not suitable to be used to calculate forecast sales of gold.